ANALISIS INVESTASI PROYEK PROPERTI PT KHARISMA KATULISTIWA HIJAU - Revi Salas Ristantri; Supriono Supriono (Politeknik Sawunggalih Aji, 2020)
Indonesia has experienced a rapid increase in investment activities, for example in Kebumen. In line with the growth of investment, it is necessary to provide quality residential facilities, housing as one of the real estate products in the form of buildings which is an alternative choice.Investment to be profitable if the investment can make investors benefit. In the business world requires a more accurate business feasibility measurement system by displaying the data as supporting evidence and calculated according to the reality of either experiencing a deficit or surplus, so as to increase the confidence of prospective investors to invest in the company. This study aims to determine the results of the analysis of investment feasibility of property projects of PT Kharisma Katulistiwa Hijau uses profit data in 2018 in assessing investment profitability using the Net Present Value (NPV), Payback Period (PP), and Internal Rate of Return (IRR) methods. The results of this study indicate that investment in property projects that are executed are worthy, with the results of the Net Present Value (NPV) of Rp 79,478,735.19 (positive value), Payback Period (PP) for 6 months 28 days, which is faster than the investment age of 12 month, Internal Rate of Return (IRR) of 9.45% /month where the bank deposit interest is 6% so that the investment is worth receiving.